2019
DOI: 10.1371/journal.pone.0219629
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant proteins of Plasmodium malariae merozoite surface protein 1 (PmMSP1): Testing immunogenicity in the BALB/c model and potential use as diagnostic tool

Abstract: Background Plasmodium malariae is the third most prevalent human malaria-causing species and has a patchy, but ample distribution in the world. Humans can host the parasite for years without presenting significant symptoms, turning its diagnosis and control into a difficult task. Here, we investigated the immunogenicity of recombinant proteins of P . malariae MSP1. Methods Five regions of PmMSP1 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In the present study, we used five recombinant antigens derived from the MSP1 protein of this parasite species. The recombinant proteins were designed as GST-fusion proteins and successfully used with human sera in a previous epidemiological study [ 6 ]. With these five recombinant proteins of P. malariae MSP1 (PmMSP1 F1, PmMSP1 F2, PmMSP1 F3, PmMSP1 F4, PmMSP1 19 ), as well as with those of P. falciparum (PfMSP1 19 ) and P. vivax (PvMSP1 19 ), we found that about 40% of the NHP sera, from different areas in Brazil, were reactive to the recombinant antigens, with PmMSP1 F1 being the most frequently detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used five recombinant antigens derived from the MSP1 protein of this parasite species. The recombinant proteins were designed as GST-fusion proteins and successfully used with human sera in a previous epidemiological study [ 6 ]. With these five recombinant proteins of P. malariae MSP1 (PmMSP1 F1, PmMSP1 F2, PmMSP1 F3, PmMSP1 F4, PmMSP1 19 ), as well as with those of P. falciparum (PfMSP1 19 ) and P. vivax (PvMSP1 19 ), we found that about 40% of the NHP sera, from different areas in Brazil, were reactive to the recombinant antigens, with PmMSP1 F1 being the most frequently detected.…”
Section: Discussionmentioning
confidence: 99%
“…GST and GST-recombinant fusion proteins of PmMSP1 (PmMSP1 F1 , PmMSP1 F2 , PmMSP1 F3 , PmMSP1 F4 , PmMSP1 19 ), P. vivax (PvMSP1 19 ) and P. falciparum (PfMSP1 19 ), representing the polymorphic N-terminal (MSP1 F1 ), the central (MSP1 F2 , MSP1 F3 , MSP1 F4 ) and the conserved C-terminal (MSP1 19 ) regions [ 6 ], were used for detecting anti-parasite antibodies in the sera samples. The GST and GST-fusion proteins were purified on glutathione-Sepharose 4B (GE Healthcare, MilliporeSigma, St. Louis, MO, USA) and the protein concentration was determined with the Bradford protein Assay (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the recognition of PmMSP1 19 was evaluated by ELISA using serum from Brazilian individuals diagnosed with malaria due to Pm (n = 16) in parallel with sera from patients with unrelated diseases (n = 21), or healthy donors (n = 15), reaching 100% sensitivity and specificity. On the other hand, sera from Pv or Pfinfected individuals did not react at all against recombinant PmMSP1 19 protein (Elizardez et al, 2019). All three MSP1 19 antigens (Pf, Pv and Pm) were recently used as bound-antigens in ELISA assays that were performed to evaluate the seroprevalence of these Plasmodium species in Suriname (Labadie-Bracho et al, 2020).…”
Section: Rdt Typesmentioning
confidence: 99%
“…of different infectious and parasitic diseases, that GST-tagged recombinant antigens have comparable cross-reactivity, specificity and antigenicity compared with untagged antigens, (e.g. [23][24][25][26][27][28][29][30]). In accordance, the specificity of the GST-tagged 2B2t recombinant antigen was actually higher than the specificity of the non-tagged 2B2t antigen (95.8% vs. 77.8%), and the cross-reactivity with sera from patients with AE was lower for the GST-2B2t compared with the 2B2t antigen (38.7% vs. 44%).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%